Conflict Management from a Spiritual Leadership Perspective - Amaludin, Asep; Rizky, Arfiani; Fintani, Pubita Sasti (International Journal Labs, 2023)
Changes in conditions that are so fast demand a shift in management, as well as mosques, mosques are an entity that has the opportunity to follow a shift in management model, this triggers conflict. This study aims to determine conflict management in the perspective of transformational leadership (a case study of the Al-Musthofa Bogor mosque) conducted by DKM Al-Musthofa Bogor City. The type of research used is descriptive qualitative. The results of the research and analysis that have been carried out can be concluded that conflicts occur between young people and old people regarding the issue of contributions that do not agree between young people and old people. This is based on the main source of conflict, namely communication jammed between the two parties. The results of this conflict management The conflict manager in this case by using a transformational leadership style is able to collaborate on ideas, roles and performance from old people and young people so that both parties can contribute side by side so as to obtain a win-win conflict solution. Both parties benefited and managed to get what they wanted.